Diagnosis of Giardia duodenalis Infection using Dot Blot in Comparison with Microscopy - Yazdani, Hajar; Maryam Sharafi, Seyedeh; Yousefi, Hoseynali; Hadipur, Mahbobeh; Sepahvand, Akram; Yousofi Darani, Hossein (Infectious Disorders - Drug Targets, 2016)
Background and Purpose: Giardia duodenalis is an intestinal flagellate parasite which spreads all over the world and is considered as a health problem in the most rural and low sanitation areas. Many diagnostic tests have been developed for the detection of Giardia parasite in stool samples but all of them have some disadvantages such as lack of sensitivity and specificity. In search for a simple and accurate test, diagnosis of Giardia infection using dot blot method has been investigated in this work. Materials and Methods: In this descriptive study, 30 stool samples which their infection with Giardia were confirmed by direct examination and formalin ether considered as case group. Thirty stool samples without Giardia infection according to formalin ether examination were also considered as a control group. Giardia cysts were isolated from the stool samples using sucrose method. In order to raise antiserum against Giardia cysts, the purified cysts were then sonicated and injected to a rabbit. A mono specific antiserum against the 66KDa band of Giardia cyst antigen was also prepared. The two antisera were used in the dot blot test. Finally, the sensitivity and specificity of the dot-blot method were estimated by considering formalin ether as the gold standard. Results: When Poly specific antiserum was used, the sensitivity and specificity of the dot blot for detection of Giardia infection were 77% and 64% respectively. However the sensitivity and specificity of this assay were 97% and 64% respectively when monospecific antiserum was used. Conclusion: It seems that dot blot is an easy method for the diagnosis of Giardia especially in the rural areas. However more work is recommended for further development of this test.
Keywords: giardia lamblia